The shopping mall servicescape affects customer satisfaction - Juhari, Nur Hafizah (2012)
A comprehensive, attractive and well-functioning physical environment of the ‘servicescape’ in shopping malls can affect the level of customer satisfaction. Furthermore, issues with the servicescape in shopping malls, such as fewer parking spaces, dysfunctional closed-circuit television (CCTV), lack of proper signage, unattractive layout and lack of ambience will decrease the number of customers. Most of the previous studies have focussed on a very specific element of the servicescape. This study discusses the combination of all relevant elements in the shopping mall’s servicescape. Thus, the purpose of this study is to provide the basic needs in facilitating the servicescape positioned on customer perception and expectations. This paper reviews the relevant elements in the shopping mall’s servicescape. Most of the literature suggested that appropriate servicescapes would provide an attraction to customers. Therefore, shopping mall managers should consider their allocation of the servicescape in the shopping mall. Further studies should investigate shoppers’ expectations in providing servicescape facilities, as the servicescape elements may not be consistent within different shopping malls.